The Circadian Clock Is Sustained in the Thyroid Gland of VIP Receptor 2 Deficient Mice - Georg, Birgitte; Fahrenkrug, Jan; Jørgensen, Henrik L.; Hannibal, Jens (Frontiers in Endocrinology, 2021)
VIP/VPAC2-receptor signaling is crucial for functioning of the circadian clock in the suprachiasmatic nucleus (SCN), since the lack results in disrupted synchrony between SCN cells and altered locomotor activity, body temperature, hormone secretion and heart rhythm. Endocrine glands, including the thyroid, show daily oscillations in clock gene expression and hormone secretion, and SCN projections target neurosecretory hypothalamic thyroid-stimulating hormone (TSH)-releasing hormone cells. The aim of the study was to gain knowledge of mechanisms important for regulation of the thyroid clock by evaluating the impact of VIP/VPAC2-receptor signaling. Quantifications of mRNAs of three clock genes (Per1, Per2 and Bmal1) in thyroids of wild type (WT) and VPAC2-receptor deficient mice were done by qPCR. Tissues were taken every 4th h during 24-h 12:12 light-dark (LD) and constant darkness (DD) periods, both genders were used. PER1 immunoreactivity was visualized on sections of both WT and VPAC2 lacking mice during a LD cycle. Finally, TSH and the thyroid hormone T4 levels were measured in the sera by commercial ELISAs. During LD, rhythmic expression of all three mRNA was found in both the WT and knockout animals. In VPAC2-receptor knockout animals, the amplitudes were approximately halved compared to the ones in the WT mice. In the WT, Per1 mRNA peaked around “sunset”, Per2 mRNA followed with approximately 2 h, while Bmal1 mRNA was in antiphase with Per1. In the VPAC2 knockout mice, the phases of the mRNAs were advanced approximately 5 h compared to the WT. During DD, the phases of all the mRNAs were identical to the ones found during LD in both groups of mice. PER1 immunoreactivity was delayed compared to its mRNA and peaked during the night in follicular cells of both the thyroid and parathyroid glands in the WT animals. In WT animals, TSH was high around the transition to darkness compared to light-on, while T4 did not change during the 24 h cycle. In conclusion, sustained and identical rhythms (phases and amplitudes) of three clock genes were found in VPAC2 deficient mice during LD and DD suggesting high degree of independence of the thyroid clock from the master SCN clock.